2018
DOI: 10.1007/s11657-018-0538-1
|View full text |Cite
|
Sign up to set email alerts
|

Correspondence between bone mineral density and intervertebral disc degeneration across age and sex

Abstract: Purpose: While the decline of bone mineral density (BMD) in the aging spine is well established, the extent to which age influences BMD distribution within the vertebra is less clear. Measures of regional BMD (rBMD) may improve predictions of vertebral strength and suggest how vertebrae might adapt with intervertebral disc degeneration. Thus, we aimed to assess how rBMD values were associated with age, sex and disc height loss (DHL). Methods: We measured rBMD in the L3 vertebra of 377 participants from the F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 46 publications
0
33
0
Order By: Relevance
“…IDD can have a large impact on the livelihood of patients and their economic development ( 1 ). IDD disrupts the distribution and density of the aged bone tissues in vertebrae ( 2 ). Nucleus pulposus (NP) mesenchymal stem cells (MSCs) can promote the regeneration of intervertebral discs due to their endogenous repair function ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…IDD can have a large impact on the livelihood of patients and their economic development ( 1 ). IDD disrupts the distribution and density of the aged bone tissues in vertebrae ( 2 ). Nucleus pulposus (NP) mesenchymal stem cells (MSCs) can promote the regeneration of intervertebral discs due to their endogenous repair function ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with prevalent fractures generally present with lower integral and trabecular vBMD than controls, (9,38) a relationship that is anticipated given the relationship between declining vBMD (35,39,40) and increasing fracture rates with age. (41,42) In line with these findings, we observed that individuals with a prevalent fracture presented with approximately 20% lower integral (134 versus 165 mg/cm 3 ) and trabecular (96 versus 119 mg/cm 3 ) vBMD at the L 3 level (Table 1).…”
Section: Discussionmentioning
confidence: 91%
“…Additionally, although measures of areal BMD and trabecular bone score in this population would be beneficial to directly compare its association with prevalent fractures versus our QCT‐derived vBMD measures, DXA was not available within 1 year of the QCT scan for all participants in our study, making this direct comparison not possible for this manuscript. Our sample size was insufficient to adequately power subsequent delineation of the effect of sex, despite the known effects of sex on the age‐dependent decline of vBMD and fracture rates . Finally, the image processing steps in our approach are currently time consuming, limiting clinical utility at this time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations